ABIDE Delphi study: topics to discuss in diagnostic consultations in memory clinics - Agnetha D. Fruijtier (Alzheimer’s Research & Therapy, 2019)
Abstract Background Information given to patients and caregivers during the clinician-patient encounter varies considerably between memory clinic professionals. Patients and caregivers express a clear desire for more information. It is unclear what information patients and caregivers value most during the diagnostic process and whether this is concordant with professionals’ opinion. We aimed to identify a topic list on which health care professionals, patients, and caregivers agree that these should be discussed during diagnostic consultations in memory clinics. Further, we aimed to establish the optimal moment for each topic to be discussed during the diagnostic process. Methods We performed a three-round Delphi consensus study. Professionals (N = 80), patients (N = 66), and caregivers (N = 76) rated the importance of 44 informative topics through an online questionnaire. Consensus was defined as a topic rating of 6 or 7 on a 7-point Likert scale by ≥ 75% of each panel. In round 2 and 3, a survey was added to identify the optimal moment during the diagnostic process to discuss each topic. Results By round 3, consensus was achieved on 17 topics divided into four categories, information about (1) diagnostic testing, (2) test results, (3) diagnosis, and (4) practical implications. Eight additional topics showed significant differences between panels. Most notable panel differences regard the risk for developing dementia and the distinction between Alzheimer’s disease and dementia, which patients and caregivers evaluated as more important compared to professionals. The optimal moment to discuss topics during the diagnostic process was identified for the 17 core topics, and the eight topics with significant differences. Conclusions We present a core list of informative topics, which professionals, patients, and caregivers agree they should be discussed during the diagnostic process in a memory clinic. The topic list can support professionals and empower patients and caregivers during diagnostic physician-patient consultations.